ANALISIS EXPECTED RETURN DAN STANDAR DEVIASI PADA SAHAM LQ45 SEKTOR E-COMMERCE - Ramadhina Anjani Nasution; Ananda Nafisa Shania Faita; Nathania Steffanie Darmawan; Anisa Sofieta (Draf Solusi Indonesia, 2025)
This research aims to evaluate the performance of stocks in the e-commerce sector listed in the LQ45 index, especially at PT Gojek Tokopedia Tbk (GOTO) and PT Bukalapak Tbk (BUKA), with an emphasis on calculating expected return and standard deviation during 2019 to 2023. The data used is taken from daily stock prices that have been adjusted based on various factors such as dividends and stock splits. The method used in this study is the Capital Asset Pricing Model (CAPM) to determine the expected return, as well as the standard deviation formula to assess the risk level. The results of the analysis showed that both stocks experienced capital loss, with the expected return reaching -223,63% for GOTO and -275,92% for BUKA. However, the risk indicator shown by the standard deviation shows a significant difference, where GOTO has a standard deviation of 0.0589 which is higher than BUKA which is 0.0489. This indicates that GOTO stock is experiencing greater fluctuations, so the risk faced by investors is also higher than BUKA. This study reveals that market instability, increased systematic risk, and macroeconomic factors contribute to a decrease in stock prices and an increase in risk. This finding is expected to be a guideline for investors to understand the risk profile and potential profit of e-commerce stocks, as well as providing views for academics and regulators to support the development of the Indonesian capital market in the growing sector.